Τρίτη, 28 Οκτωβρίου 2014

$a·a’=b·b’+c·c’$

Να αποδειχθεί ότι:
$a·a’=b·b’+c·c’$.

3 σχόλια:

  1. (a+a')^2=(b+b')^2+(c+c')^2 μετά από πράξεις το ζητούμενο

    ΑπάντησηΔιαγραφή
  2. $(b+b')^2+(c+c')^2=(a+a')^2$ →
    $b^2+b^'2 +2bb'+c^2+c'^2+2cc'=a^2+a'^2+2aa'$
    Όμως $b^+c^2=a^2 και b'^2+c'^2=a'^2$, άρα
    $2aa'=2(bb'+cc')$ → $aa'=bb'+cc'$

    ΑπάντησηΔιαγραφή
  3. $(b+b')^2+(c+c')^2=(a+a')^2$ →
    $b^2+b'^2 +2bb'+c^2+c'^2+2cc'=a^2+a'^2+2aa'$
    Όμως $b^2+c^2=a^2 και b'^2+c'^2=a'^2$, άρα
    $2aa'=2(bb'+cc')$ → $aa'=bb'+cc'$

    ΑπάντησηΔιαγραφή